The effect of clay turbidity on the growth performance of white shrimp, Litopenaeus vannamei (Boone, 1931) - Lim, Eu Riang (2012)
Clay turbidity has been one of the least-studied aspects in the field of aquaculture, whether it is on fish or shrimp. This study was conducted to find out the effect of different clay turbidity on the growth of Litopenaeus vannamei in a period of 4 weeks. The clay turbidity was first determined at levels starting from 0 mg/L, followed by 50 mg/L, 100 mg/L and 200 mg/L with 200 pieces of shrimp per tank. Each treatment had four replicates. Analysis were done using one-way ANOVA followed by Duncan multiple range test, (P=0.05). Increased in the level of clay turbidity up to 200 mg/L did not adversely affect the growth performance of shrimp. NTU values, as the experiment progressed, recorded an uptrend. It was recommended that further studies to be conducted to further ascertain the findings of this study.